The Expression of IL-8 in Gingival Rattus novergicus After Exposed by Silver Gel Nano Particles 15 µg/ml - Kharinna Widowati (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2017)
Background: The uses of silver nanoparticle are growing so fast, especially in the medical science, it’s used in many kinds of concentration. In dentistry, it’s used to decrease halitosis and periodontal diseases, and also wound healing process. It can affect the viability of the cells, give the bad effects to the human’s health and environment if we use it in a long-term and in an uncertain concentration. Purpose: The aim of the study was to analysis the healing process of gingival fibroblast in Rattus novergicus after exposed by 15 µg/ml silver gel nanoparticles. Materials and Methods: This study uses 9 male wistar rats were divided into 3 groups. Group A: Cut (hurt it) in the oral gingiva and exposed to Ag-Np Gel 15 µg/ml for 3 days. After 3 days, they were sacrificed and cut the gingival fibroblast off 3x4 cm size with scalpel. Group B: cut in the oral gingiva and exposed to Ag-Np Gel 15 µg/ml for 5 days. After 5 days they were sacrificed and cut the gingival fibroblast off 3x4 cm size with scalpel. Group C: cut in the oral gingiva and exposed to none for 3 days then cut the gingival fibroblast off 3x4 cm size with scalpel. The expressions of IL-8 in the wound healing process were painted by Immunohistochemical method. This data was analyzed by using the t-test method. Results: General characteristic of IL-8 is shown in brown color immunoreactive expression on macrophage via immunohistochemical painting with monoclonal antibody anti IL-8. Mean expression numbers of IL-8 in the group A = 11,7; group B = 16,3; and group C (control) = 28,3. T-test sign.number of group A & C = 0,004; group B & C = 0,000. Conclusion: The exposure of 15 µg/ml silver gel nanoparticle to gingival fibroblast of Rattus novergicus reduces the expressions of IL-8 in the day-3 and day-5 post exposure. So, it may accelerate the wound healing process.